IMPLEMENTASI KNOWLEDGE SHARING (BERBAGI PENGETAHUAN) DI KALANGAN PUSTAKAWAN - Noorika Retno Widuri (Central Library of Universitas Sebelas Maret, 2018)
Sharing knowledge in principle is a learning opportunity for the destitute. Sharing knowledge is part of the knowledge management process. Through sharing knowledge, it is expected to increase knowledge, experience and grow as well as develop new ideas. Sharing knowledge can only be done when each member has a wide opportunity in discussions, ideas, criticisms and comments to other members. Knowledge sharing between librarians both in organizations related internally and between organizations is important. Because the existence of sharing, librarians will add insight into the activities that are in the approval increase. This activity can be carried out routinely depending on the policies of the library leader. The Culture of Knowledge Sharing among librarians must be developed and continue to be developed. Sharing, will add insight into various activities and the development of knowledge about librarianship. Sharing activities, can be done regularly and periodically. Knowledge sharing creates a positive climate for librarians. In addition to increasing knowledge, it is also a means of communication between librarians.